The Functions and Benefits of the ePortfolio in Craft Education at the Primary Leve - Saarinen, Auli; Seitamaa-Hakkarainen, Pirita; Hakkarainen, Kai (Design and Technology Education: An International Journal, 2016)
The authors investigated primary school pupils’ experiences using an electronic portfolio in their craft education for a three year period, from the 3rd grade until the end of the 5th grade. This article emphasizes the functions and the benefits of the ePortfolio method and outlines general user experiences based on pupil interviews (N=38), which recounted user experiences from the start of subject teaching in the 3rd grade. Data-driven content analysis with a summative approach was used to analyse these interviews. The results indicate that an ePortfolio (realized through the iPad application, Book Creator) is a workable method in craft education. When the use begins during the early school years, it is experienced as a natural part of the work process. The identified key functions were collection and management of information, communication and verification of development. The experienced benefits were related to supporting the working process; activities documented by the ePortfolio appeared to operate as stimuli to memory and elicited rehearsing of concepts in a way that deepened understanding of the past experiences. The ePortfolio method offers a balancing opportunity to regard design and making process in assessment. Despite being based on the pupils’ experiences, the results are relevant and useful for teachers when improving their pedagogical practices.